Modeling and Design of a Multistream Plate-Fin Heat Exchanger in the Air Separation Units by Pinch Technology - Nazar Oudah Mousa Alyaseen; Salem Mehrzad; Mohammad Reza Saffarian (International Journal of Chemical Engineering)
Recent years have seen considerable advancement in cryogenic technology. Air separation devices have used the cold box with heat exchanger plate-fin (PFHE) in numerous applications. Cryogenic technologies are used in many industrial processes to recover heat and reduce energy consumption. The multistream plate-fin heat exchanger (MSPFHE) is heavily utilized in the air separation plant’s (ASU) design. The plate-fin heat exchanger, one of the most important applications in the cryogenic industry, is the focus of the current investigation. The air entering this operation has been cooled by utilizing energy from streams originating from the distillation tower in the air separation unit (ASU) to reduce energy usage. The project aims to develop and create a multistream plate-fin heat exchanger (MSPFHE) that may be used in the cold box of an air separation unit practically and without limitations. The pinch technique, a method based on the usage of composite curves, was used in the creation of MSPFHE. With pinch technology, it is possible to divide a multistream exchanger into block portions that represent enthalpy intervals and identify the entry and departure sites for the streams. The correlations used in the MSPFHE thermal design model were first modeled and compared to earlier models as part of this effort. This model has been turned into MATLAB code and utilized in two case studies to yield acceptable results during the sizing step. Calculations of thermodynamic properties, heat transfer, pressure drop, choice of fin type, and final heat exchanger size were all part of the design of the MSPFHE. Finally, based on the software’s ability to reproduce the identical environmental conditions nature produces, the case study results have been validated using Aspen EDR. These findings were matched to findings from the literature and determined to be reliable and consistent.